Meat Production Potential of Local Horse Breeds: Sustainable Conservation Through Valorization - Ante Ivanković; Mateja Pećina; Giovanni Bittante; Nicoló Amalfitano; Miljenko Konjačić; Nikolina Kelava Ugarković (Animals)
Local horse breeds, particularly cold-blood types, are often marginalized in economic and social contexts, primarily due to the neglect of their economic, genetic, and cultural potential, as well as their role in preserving the identity of rural areas, local communities, and ecosystems. The valorization of these breeds is a crucial prerequisite for their economic repositioning. The Croatian Posavina horse is a local breed, well adapted to harsh, extensive production systems. Its sustainability is achieved through pasture-based meat production, primarily targeting foreign European markets. Ensuring the sustainability of conservation programs requires a thorough understanding of growth dynamics, carcass traits, and meat quality. This study assessed growth performance and carcass characteristics in a sample of 30 male foals, with ten animals selected for detailed analysis of fatty acid, amino acid, and volatile aromatic compound profiles. At eleven months of age, the foals reached a live weight of 347 kg and a dressing percentage of 60.62%. Color, tenderness, and water-holding capacity parameters were favorable for consumers. The meat’s high protein content (22.37%) and low intramuscular fat (3.61%) make it suitable for health-conscious or sensitive consumer groups. A high proportion of polyunsaturated fatty acids (28.5%) and a nutritionally balanced ω-6/ω-3 ratio (3.46) highlight the meat’s functional properties. The essential-to-non-essential amino acid ratio (0.81) further supports its nutritional value. Sensory analysis confirmed an attractive appearance, desirable texture and flavor, and a rich aromatic profile. The carcass and meat quality results, when compared with the production traits of other horse breeds, indicate that Croatian Posavina foal meat is a high-quality and nutritionally valuable alternative to conventional red meat. With optimized conservation and production strategies, the Croatian Posavina horse holds strong potential for market repositioning within sustainable and functional meat production systems.